"Turning The Tables": A Technical Tip to Overcome Anatomic Constraints While Distal Locking During Femur Intramedullary Nailing. Issue 4 (25th December 2022) - Mittal, Samarth; Trikha, Tanya; Karpe, Aashraya; Vatsya, Pulak; Trikha, Vivek
Abstract : Introduction: Interlocking nailing for femoral shaft fractures is one of the most common surgeries by orthopedic traumatologists. With the advent of cephalon-medullary nailing, a center-center position of the head screw has become mandatory. With retroversion or reduced anteversion of neck, a center placement needs internal rotation of the nail. This makes distal locking problematic, as now making a perfect circle is difficult due to the physical constraints of C-arm rotation. Objective: To describe a novel technique to overcome the anatomic constraints and get a perfect circle for quick distal locking. Material and Methods: We used a novel technique in our routine femur nailing cases. Here, in cases with reduced anteversion of the neck, distal locking was tenuous due to difficulty in making a perfect circle. Thus, we have used a new technique called "Turning the table" where we externally rotate the table, which allows us to get a perfect circle for locking in almost a single exposure. Results: This is a useful technique in cases where getting a perfect circle is difficult due to anatomic constraints and variations and can help in getting a perfect circle with limited radiation exposure.